2013
DOI: 10.4103/2152-7806.109810
|View full text |Cite
|
Sign up to set email alerts
|

Use of stent-assisted coil embolization for the treatment of wide-necked aneurysms: A systematic review

Abstract: Background:The use of stent-assisted coiling (SAC) has been shown to be a treatment option for complex aneurysms. We reviewed systematically the immediate and mid-term angiographic results following treatment of wide-necked aneurysms with self-expanding stents and coils, as well as the peri- and postprocedural rate of complications.Methods:A computerized database search was conducted from 01/2000 to 04/2011 using appropriate indexed terms on Pubmed. Inclusion criteria were: (1) homogeneous populations of ≥10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 99 publications
3
11
2
1
Order By: Relevance
“…It must be noted that despite the improvement of angiographic outcome in SAC group, almost half of aneurysms in both groups were still incompletely occluded with persisting risk of rupture. Our rate of complete aneurysm occlusion (56.2% in SAC group and 50.5% in NAC group) was lower than a previously published rate (61%-71.9% for SAC and 61.5% for NAC) ( 27 - 29 ), but this did not lead to an increased rate of delayed rupture or re-rupture (0.9% of all coiled aneurysms in our institution).…”
Section: Discussioncontrasting
confidence: 83%
“…It must be noted that despite the improvement of angiographic outcome in SAC group, almost half of aneurysms in both groups were still incompletely occluded with persisting risk of rupture. Our rate of complete aneurysm occlusion (56.2% in SAC group and 50.5% in NAC group) was lower than a previously published rate (61%-71.9% for SAC and 61.5% for NAC) ( 27 - 29 ), but this did not lead to an increased rate of delayed rupture or re-rupture (0.9% of all coiled aneurysms in our institution).…”
Section: Discussioncontrasting
confidence: 83%
“…Some studies have suggested the SAC results in improved outcomes [35][36][37] while some have found similar results to stand-alone coiling [38][39][40][41]. A systematic review of multiple studies found the recanalization rate to be 13.2% following SAC [42], which is lower than the 20% reported for stand-alone coiling. Lawson et al found that SAC not only had improved recurrence rates but also promoted progressive thrombosis [43].…”
Section: Sacmentioning
confidence: 76%
“…Interventional treatment has gradually become an important method of aneurysm management and virtually almost 100% of aneurysms have been occluded by embolization in recent years [5]. However, with regard to widenecked and large aneurysms, current technical limitations in embolization technology have prevented complete and durable aneurysm occlusion [6]. It is generally believed that contraindications of embolization include the following: aneurysm is too small in size (<2 mm); intubation artery is with severe hardening distortions or Figure 2.…”
Section: Discussionmentioning
confidence: 99%